Impact of potassium citrate on urinary risk profile, glucose and lipid metabolism of kidney stone formers in Switzerland - Wiegand, Anna (Clin Kidney J, 2019)
BACKGROUND: Hypocitraturia and hypercalciuria are the most prevalent risk factors in kidney stone formers (KSFs). Citrate supplementation has been introduced for metaphylaxis in KSFs. However, beyond its effects on urinary parameters and stone recurrence, only a few studies have investigated the impact of citrate on other metabolic pathways such as glucose or lipid metabolism. METHODS: We performed an observational study using data from the Swiss Kidney Stone Cohort. Patients were subdivided into two groups based on treatment with potassium citrate or not. The outcomes were changes of urinary risk parameters, haemoglobin A1c (HbA(1c)), fasting glucose, cholesterol and body mass index (BMI). RESULTS: Hypocitraturia was present in 19.3% of 428 KSFs and potassium citrate was administered to 43 patients (10.0%) at a mean dosage of 3819 ± 1796 mg/day (corresponding to 12.5 ± 5.9 mmol/ day). Treatment with potassium citrate was associated with a significantly higher mean change in urinary citrate (P = 0.010) and urinary magnesium (P = 0.020) compared with no potassium citrate treatment. Exogenous citrate administration had no effect on cholesterol, fasting glucose, HbA(1c) and BMI. Multiple linear regression analysis demonstrated no significant association of 1,25-dihydroxyvitamin D(3) [1,25(OH)(2) D(3)] levels with urinary citrate excretion. CONCLUSION: Potassium citrate supplementation in KSFs in Switzerland resulted in a beneficial change of the urinary risk profile by particularly increasing anti-lithogenic factors. Fasting glucose, HbA(1c), cholesterol levels and BMI were unaffected by potassium citrate therapy after 3 months, suggesting that potassium citrate is safe and not associated with unfavourable metabolic side effects. Lastly, 1,25(OH)(2) D(3) levels were not associated with urinary citrate excretion.